ASSESSING THE ANTIBACTERIAL EFFICACY OF ETHANOL EXTRACT FROM PEPPERMINT LEAVES (Mentha piperita L.) IN HAND SOAP GEL AGAINST Staphylococcus epidermidis: UJI EFEKTIVITAS ANTIBAKTERI SEDIAAN HAND SOAP GEL EKSTRAK ETANOL DAUN PEPPERMINT (Mentha piperita L.) TERHADAP Staphylococcus epidermidis - Candrika, Candrika; Anita Naibaho, Tri; Rinanda Silitonga, Desni; putri aisyia fauzi, Ziza (FORTE JOURNAL, 2025)
In traditional medicine, peppermint leaves (Mentha piperita L.) have been empirically used to treat of illnesses, including cholesterol, gout, hypertension. Peppermint leaves are known to contain a variety of secondary metabolites, including alkaloids, flavonoids, tannins, steroids, saponins, their antibacterial properties have been demonstrated experimentally. It is well known that these substances actively prevent the growth and development of germs. The aim of this study was to evaluate the stability of the formulation of hand soap gel including peppermint leaf ethanol extract, as well as the antibacterial activity of the extract against Staphylococcus epidermidis.Using a 70% ethanol solvent, peppermint leaf ethanol extract was produced by maceration. Diffusion agar method was then used to assess the peppermint leaf ethanol extract's antibacterial activity against Staphylococcus epidermidis. Then, different amounts of 3,6,9% of peppermint leaf ethanol extract were added to Hand Soap gel formulations. the final formulations were examined for preparation properties such as homogeneity, spreadability, foaming power, physical stability at various temperatures, organoleptic testing. The study's findings demonstrated that peppermint leaf ethanol extract can stop Staphylococcus epidermidis bacteria growing. This resulted in an inhibition zone diameter of 17.1 mm at 50% concentration, 16.3 mm at 40%, 15.8 mm at 30%, 14.5 mm at 20%, 13.5 mm at 10% and 6.9 mm at the lowest concentration of 1%. The test profile demonstrates that the diameter of the inhibition zone generated increases with concentration. The Hand Soap Gel formulation satisfied the criteria for evaluating and demonstrated consistent physical stability throughout a 4-week storage period.